(untitled) (Studia Prawnicze / The Legal Studies, 2012)
Ochrona interesów konsumentów jest jednym z zadań stawianych przed organami państwa, gdyż decyduje o zachowaniu uczciwości i bezpieczeństwie obrotu gospodarczego. Ustawodawca przewidział szereg instrumentów prawnych dla skutecznej realizacji tego celu. Specyficzne unormowania zostały zawarte w ustawie z 12.06.2003 r. Prawo pocztowe, gdyż znaczna ich część odnosi się do jednej kategorii operatorów świadczących usługi pocztowe, a mianowicie operatorów publicznych. Dotyczy to w szczególności zasad odpowiedzialności i możliwości dochodzenia roszczeń w przypadku niewykonania lub nienależytego wykonania umowy usługi pocztowej. W związku z tym powstaje kwestia, czy zasady odpowiedzialności operatora publicznego należy odnosić do operatora niepublicznego, a jeżeli tak, to na jakich zasadach, co ma istotne znaczenie z punktu widzenia ochrony praw i interesów konsumentów, gdyż wpływa na ich sytuację prawną The legal status of the public operator, which is the Polish Post, as well as non-public operators, and the ability to conduct business activities by them should be considered in the context of the principles of the economic freedom and equality entrepreneurs, as expressed in the Constitution. It would suggest that all of these subjects should be treated by the legislator in the same way. However, provisions of the law postal allow conclude that the legal status of the public operator and non-public operators is different, because additional obligations were imposed on the public operator, but it also uses a number of privileges that are not available to other operators. This concerns in particular the principlesm of accountability and redress in the event of non-performance or improper performance of a contract of postal service. Therefore, the question arises, how this affects the protection of consumers’ interests, which is one of the tasks facing the state bodies, as determined by maintaining the integrity and security of business trading, while protecting the weaker party in legal relations, which undoubtedly is the consumer. This issue is important for the investigation of consumer claims for damages for harm caused by the operator in carrying out a contract of postal service. In particular, it is important to determine whether the rules on liability provided for the public operator must apply to the non-public operator, and if so, whether directly or into other way. It is necessary to take into account here, that led legislator in recognition of the public postal operator and the common postal service. On the one hand, the Polish legislator was obliged to liberalize the postal market, on the other hand, the solutions accepted by him were supposed to provide the Polish Post leadership on the market of common services, which in practice leads to monopoly. Therefore, the legal position of the consumer determines from services of which will use operators. Liability rules of the public operator and non-public operator are different for the existing damage and manners of pursuing claims. These principles are autonomous, regulated with different provisions of the law which are standardizing these issues in the different and comprehensive way.